2011
DOI: 10.1021/jp1095536
|View full text |Cite
|
Sign up to set email alerts
|

Role of Conformational Isomerism in Solvent-Mediated Charge Transfer in Chiral (S) 1,2,3,4-Tetrahydro-3-isoquinoline Methanol (THIQM): Condensed-Phase to Jet-Cooled Spectroscopic Studies

Abstract: Intramolecular charge-transfer reaction in chiral (S) 1,2,3,4-tetrahydro-3-isoquinoline methanol (THIQM) has been investigated in the condensed phase and in jet-cooled conditions by means of laser-induced fluorescence, dispersed emission, resonance-enhanced two-photon ionization, and IR-UV double resonance experiments, as well as quantum chemical calculations. In the condensed phase, THIQM only shows local emission in nonpolar and protic solvents and dual emission in aprotic polar solvents, where the solvent-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…No CT emission is observed in jet-cooled isolated THQIM because the CT state is higher in energy than the LE state when not stabilised by the solvent. Complexation with acetonitrile results in a red-shifted emission, like observed in solution, but no stereoselectivity has been observed [171]. The hydrates show more interesting properties.…”
Section: Charge Transfer In the Excited Statementioning
confidence: 91%
See 2 more Smart Citations
“…No CT emission is observed in jet-cooled isolated THQIM because the CT state is higher in energy than the LE state when not stabilised by the solvent. Complexation with acetonitrile results in a red-shifted emission, like observed in solution, but no stereoselectivity has been observed [171]. The hydrates show more interesting properties.…”
Section: Charge Transfer In the Excited Statementioning
confidence: 91%
“…Because they account for medium-range correlation, the hybrid M05-2X functional has been shown to satisfactorily describe NCIs in bio-molecular complexes, provided that they don't involve too many long-range interactions like dispersion [169,170]. They have led to good results for complexes involving mainly strong hydrogen bonds [171] but fail at describing long-range components of the interaction energy [169]. Dispersion-corrected functionals are frequently used as they combine acceptable calculation time with accurate description of dispersion [172][173][174].…”
Section: Spectroscopic Methods For Ionic Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results have shown that the proton is located on the α‐amino nitrogen of alanine . However, it has been shown that gas‐phase complexes can contain subunits that are not the most stable form of the bare entity …”
Section: Experimental and Computational Methodsmentioning
confidence: 98%
“…[18][19][20] For example, the two diastereomers of 1,2,3,4-tetrahydro-3-isoquinoline-methanol involve an OHÁ Á ÁN or an NHÁ Á ÁO interaction depending on the relative chirality of the adjacent asymmetric carbon and nitrogen atoms. 20,21 Life chemistry involves species in different pH and redox states, which motivates the study of protonated or cationic species in parallel to that of the neutral. However, few comparative studies have been reported on stereochemical effects in different charge states to assess the sensitivity of stereochemical factors (enhancement or reduction) upon ionisation or protonation.…”
Section: Introductionmentioning
confidence: 99%